Strategi Peningkatan Kinerja Dosen Pendidikan Ekonomi Unpam Di Masa Pandemi Covid-19 - Syafaatul Hidayati; Syamsul Anwar; Badrus Sholeh (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2022)
The purpose of this research is to find out the strategy for developing lecturers' performance during the COVID-19 pandemic". The research subjects were 55 lecturers of economic education at Pamulang University (UNPAM). This research was conducted by means of a literature review. In addition, the researcher also conducted semi-structured interviews with six lecturers to strengthen the research findings. In an effort to realize a quality university, of course, the development of lecturers is needed. Thus, in an effort to realize the performance of lecturers, reliable professional competencies are needed. The strategy for improving the performance of lecturers is generally based on the findings: (1) four competencies, namely pedagogic competence; (2) the form of professional lecturer competency development needed, among others, for pedagogic competence in the form of training on techniques for using learning media; (3) elements of research activities need to be redeveloped by communicating a lot with experts and attending seminars/webinars to improve abilities in research and (4) community service must be more sensitive to the needs of the place intended for service and an evaluation is carried out after the activity and needs help the latest technology in its implementation, especially in this pandemic era.